Repurposing an inhibitor of ribosomal biogenesis with broad anti-fungal activity. Issue 1 (December 2017) - Sun, Nuo; Li, Dongmei; Zhang, Yuhan; Killeen, Kyle; Groutas, William; Calderone, Richard
Abstract The lack of new antifungal compounds with unique mechanisms of action is a concern for therapeutic management of patients. To identify inhibitors against human pathogenic fungi, we screened ~3000 compounds provided by the Developmental Therapeutics Program of NIH/NCI against a panel of pathogenic fungi includingCandida species, Aspergillus fumigatus, andCryptococcus neoformans . NSC319726 (a thiosemicarbazone) had broad antifungal activity in the range of 0.1–2.0 µg/ml and was also inhibitory to fluconazole-resistant isolates ofCandida species. Synergy was demonstrated with NSC319726 and azoles, as well as caspofungin. The inhibitory concentration 50% (IC50 ) of NSC319726 was 35–800-fold higher than the Minimum Inhibitory Concentration 50% (MIC50 values), which indicates low compound toxicity to human cellsin vitro . Transcriptome analysis of treated and untreatedC. albicans using Gene Ontology (GO) revealed a large cluster of down regulated genes that encode translational proteins, especially those with ribosome biogenesis functions. As NSC319726 was first shown to have anti-cancer activity, its affects against human pathogenic fungi establish NSC319726 as a repurposed, off-patent compound that has potential antifungal activity. The minimalin vitro toxicity of lead optimized NSC319726 and its reasonable inhibitory activity against pathogens suggest advancing this compound toin vivo toxicity testing and protection studies against candidiasis.